Efectos de las instrucciones audiovisuales no explícitas sobre el comportamiento alimentario (2010)
This study evaluated the effects of non-explicit audiovisual instructions on feeding behaviour. Five adults between 19 and 24 years-old participated as subjects, which were exposed at nutritional (fruit and water) or no nutritional (chips and soda) foods during two experimental phases. Subjects were videotaped and exposed to two video programs in different phases. In the first phase, subjects were exposed to a musical video, in the second phase subjects were exposed to a program about health eating habits. The results showed that non-explicit audiovisual instructions modified feeding behaviour. However, will be necessary evaluate if these modification could persist for longer time.